Succinate dehydrogenase inhibitor seed treatments positively affect the physiological condition of maize under drought stress - Radzikowska, Dominika; Kowalczewski, Przemysław Łukasz; Grzanka, Monika; Głowicka-Wołoszyn, Romana; Nowicki, Marcin; Sawinska, Zuzanna (Frontiers in Plant Science, 2022)
Improvements in agricultural production are needed, as the growing human population demands more resources and exerts stronger effects on climate. Water scarcity is one of the main factors limiting the yield of maize in many regions of the world. One possible method to mitigate the negative effects of drought are seed mortars, improving plant development from the early stages onwards. In this study, we tested 12 various seed treatments with and without succinate dehydrogenase inhibitors (SDHI; sedaxane) on maize ‘SY Fanatic’. Physiological parameters of germinating seeds, of young maize seedlings under drought, and of seedlings recuperated from drought were assessed and compared across 12 seed treatments and with non-stressed plants. The seed treatments varied greatly in their influence on the germination and the physiological state of seedlings under drought and after regeneration. Seeds under treatments No. 6, 11, and 12 showed the highest germination energy (97.3%). The use of SDHI-containing seed treatments significantly improved the development of the maize root system. The longest roots, approx. 13 cm in length, were recorded for treatments No. 6 and 12, both containing sedaxane. These treatments also boosted the functioning of plants growing under optimal soil moisture conditions and under drought stress, influencing the photosynthesis process, increasing the absorption of CO2, and improving the parameters of chlorophyll fluorescence in relation to non-treated controls. Our data indicated that using substances from the SDHI group can possibly reduce the drought-related stress reactions in maize, helping this important crop to face the progressing climate change.